The influence of climate change related factors on the response of two clam species to diclofenac - Costa, Silvana (2020)
Diclofenac (DIC) is one of the non-steroidal anti-inflammatory drugs (NSAID) with higher consumption rates, used in both human and veterinary medicine. Previous studies already demonstrated the presence of this drug in aquatic environments and adverse effects towards inhabiting organisms. However, with the predictions of ocean acidification and warming, the impacts induced by DIC may differ from what is presently known and can be species-dependent. Thus, the present study aimed to comparatively assess the effects caused by DIC in the clams Ruditapes philippinarum and Ruditapes decussatus and evaluate if these impacts were influenced by pH and temperature. For this, organisms were acclimated for 30 days at two different temperature and pH (control conditions: pH 8.1, 17 °C; climate change forecasted scenario: pH 7.7, 20 °C) in the absence of drugs (experimental period I) followed by 7 days exposure under the same water physical parameters but in absence or presence of the pharmaceutical drug (at 1 μg/L, experimental period II). Biochemical responses covering metabolic capacity, oxidative stress and damage-related biomarkers were contrasted in clams at the end of the second experimental period. The results showed that under actual conditions, R. philippinarum individuals exposed to DIC presented enhanced antioxidant activities and reduced their respiration rate compared with non-contaminated clams. When exposed to the predicted climate change conditions, a similar response was observed in contaminated clams, but in this case clams increased their metabolic activities probably to fight the stress caused by the combination of both stressors. When R. decussatus was exposed to DIC, even at actual pH and temperature conditions, their antioxidant defences were also elevated but their baseline enzymatic activities were also naturally higher in respect to R. philippinarum. Although clams may use different strategies to prevent DIC damage, both clam species showed under low pH and high temperature limited oxidative stress impacts in line with a lower DIC bioaccumulation. The present findings reveal that predicted climate change related factors may not enhance the impacts of DIC in Ruditapes clams in a species-dependent manner although both displayed particular mechanisms to face stress.